2019
DOI: 10.1073/pnas.1907810116
|View full text |Cite
|
Sign up to set email alerts
|

Role of striatal ΔFosB in l -Dopa–induced dyskinesias of parkinsonian nonhuman primates

Abstract: Long-term dopamine (DA) replacement therapy in Parkinson’s disease (PD) leads to the development of abnormal involuntary movements known asl-Dopa–induced dyskinesia (LID). The transcription factor ΔFosB that is highly up-regulated in the striatum following chronicl-Dopa exposure may participate in the mechanisms of altered neuronal responses to DA generating LID. To identify intrinsic effects of elevated ΔFosB onl-Dopa responses, we induced transgenic ΔFosB overexpression in the striatum of parkinsonian nonhum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…In the present study, up to the 1, 4, and 17 months after the treatment with the α-syn PFFs, we did not observe dopaminergic neuron loss in the substantia nigra, nor motor and cognitive dysfunction (Supplementary Fig. 7 ) in consistent with the previous report 43 , but rather, only detected signs of dopaminergic neurodegeneration, i.e., reduced TH intensity and axonal swelling in the putamen 44 46 . Interestingly, an increase in the iron content was detected in the brains of monkeys in the PD model groups and further studies revealed that the increased iron was mainly deposited in the substantia nigra and globus pallidus, which are also the brain regions that exhibit lesions in PD patients 47 51 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, up to the 1, 4, and 17 months after the treatment with the α-syn PFFs, we did not observe dopaminergic neuron loss in the substantia nigra, nor motor and cognitive dysfunction (Supplementary Fig. 7 ) in consistent with the previous report 43 , but rather, only detected signs of dopaminergic neurodegeneration, i.e., reduced TH intensity and axonal swelling in the putamen 44 46 . Interestingly, an increase in the iron content was detected in the brains of monkeys in the PD model groups and further studies revealed that the increased iron was mainly deposited in the substantia nigra and globus pallidus, which are also the brain regions that exhibit lesions in PD patients 47 51 .…”
Section: Discussionsupporting
confidence: 93%
“…In Parkinsonian rat, local administration of L -DOPA in the striatum induces dyskinesia ( Buck et al, 2010 ). Further immediate-early genes such as c-Fos, FosB, and ΔFosB are consistently upregulated in the striatum of animals with LID ( Cenci, 2002 ; Beck et al, 2019 ). Detailed information about the involvement of the striatum in LID can be found in other articles ( Cenci et al, 2018 ; Zhai et al, 2019 ).…”
Section: Possible Loci Of Circuit Modulation In Lidmentioning
confidence: 99%
“…Among others, This transcription factor regulates genes responsible for plasticity in striatal neurons. Elevated levels of ΔFosB are associated with loss of function of FosB, which results in early development of dyskinesia and unstable firing rate changes during ON phase in L-DOPA treated animals [69]. MSH1 histone kinase activity also increases with ΔFosB levels, consistent with MSK1's target, histone H3.…”
Section: Fosb Transcription Factormentioning
confidence: 71%